The Secret of Brahms Cellos Sonata No. 1 Op. 38 and Shostakovich Cello Sonata Op. 40 - Asep Hidayat Wirayudha (Graduate School of Institut Seni Indonesia Yogyakarta, 2016)
This study aims to find a technique solution behind the Far interval and Octave interval in Brahms Cello sonata no.1 opus 38 and Shostakovich cello sonata op. 40 through literature and Discography approach. The fingering problems may poses special difficulties to any cellists. According to the author’s assessment, there are two problems that warrant special attentions of the cellist. Both intervals may cause serious problems on the performance of short fingers cellists. The size of the fingerboard on the cello as compared to other string instruments are longer, resulting in harder difficulties regarding obtaining tone (Stowell, 1999). From the results of the Far Interval and Octave Interval and active involvement of the researchers, the results show that, what is shown that every cellist are anatomically different. The fingers of the cellists are naturally very flexible. It cannot be converted to another cellists. So flexibly that it is possible to overcome the problem in a simple and convenient.